BUSINESS FEASIBILITY STUDY OF GAPURA RESTAURANTIN NUSA DUA – BALI - Komang Handi Dwi Darma Santhi; Sonny Sonny (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
Restaurant as one of the culinary businesses can be categorized as an industry with a promising profit.Gapura restaurant which is planned to open in 2021 at Nusa Dua – Bali, represents the concept to serve the real exquisite food taste from Bali. The objective of this study is to analyze the business feasibility of the Gapura restaurant in the scope of marketing and finance. To analyze the scope of marketing and finance, the researcher uses qualitative and quantitative analysis.For marketing scope, the researcher using Porter’s Five Forces analysis and SWOT analysis. For financial aspects, the researcher uses Net Present Value (NPV), Payback Period (PP), and profitability ratio analysis (for 5 years). For the result in marketing, it is founded that the price offered for the menu in this restaurant is relatively cheaper than its competitor and committed to support less plastic movement through its packaging system. The result of the financial analysis: payback period approximately within 3 years 4 month and Net Present Value at Rp1,407,994,472. After the marketing analysis and calculations were made, it can be concluded that the business of the Gapura restaurant is feasible to run. Keywords: Feasibility study, SWOT Analysis, Payback Period, Net Present Value, Profitability Ratio